EP384/#926 Cost-analysis of an enhanced recovery program after minimally invasive gynecologic oncology surgery. (4th December 2022) - Mitric, Cristina; Kim, Soyoun Rachel; Nelson, Gregg; Laframboise, Stephane; Mccluskey, Stuart; Avery, Lisa; Kujbid, Nastasia; Zia, Aysha; Spenard, Elisabeth; Bernardini, Marcus; Ferguson, Sarah; May, Taymaa; et al.
Abstract : Objectives: A perioperative quality improvement initiative for minimally invasive (MIS) gynecologic oncology surgery at our centre improved the rate of same day discharge (SDD) from 29% to 75%. The current study aims to estimate the project implementation costs and compare costs between the pre-intervention and post-intervention cohorts. Methods: Our Early Recovery After Surgery (ERAS)-based perioperative program enrolled 102 consecutive patients undergoing MIS hysterectomy at a single cancer centre during a 12-month period, and their SDD rates were compared to a historical cohort of 100 consecutive patients. Surgical admissions and readmissions were collected from the case-cost department. Postoperative and unplanned clinic visits, and emergency room visits costs were estimated from average visit cost. Total costs were calculated from the surgical visits, readmissions, and all 30 days postoperative visits at our institution, with the addition of implementation cost in the post-intervention group. Results: The total cost per patient was 10 357.41 post-intervention compared to 12420.65 pre-intervention (p=0.01), resulting in a 17% total hospital cost reduction per patient, specifically 2063.24. The total cost for the program implementation was 134.34 per patient for a total cost of 13 106.52. The average surgical admission cost per patient post-intervention was 9859.80 compared to 12 122.88 pre-intervention (p=0.01). The mean costs for readmission and outpatient clinical visits were 221.93 vs. 157.53, and 140.56 vs. 133.44 for post- and pre-intervention respectively. Conclusions: A quality-improvement ERAS initiative in gynecology oncology MIS led to a 17% total cost reduction per patient for a total saving of 2063.24 per patient.